Why Has Unemployment in Algeria Been Higher than in MENA and Transition Countries? - Kpodar, Kangni (IMF Working Papers; Working Paper ;, 2007)
This paper analyzes the determinants of labor market performance in Algeria. When the model is estimated with panel data on a sample of MENA and transition countries for 1995- 2005, the results suggest that lower growth in labor productivity in Algeria is associated with higher unemployment than the sample average, though recent positive terms of trade shocks have helped Algeria reduce the differential. Labor market rigidities and labor taxation do not seem to explain why unemployment is higher in Algeria than in other countries. The results are robust to various panel econometric methods and instrumental variable estimates.